„Niechaj nam w Jasełkach nikt nie przedstawia, że Jezus urodził się w Palestynie” – „Betlejem polskie” Lucjana Rydla jako szopka literacka - Moroz , Agata (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The article is focused on Lucjan Rydel as the author of Polish Bethlehem - a nativity play in which its author saw the most perfect form of folk theatre, a concept he himself keenly propagated. The central issue here is an attempt to observe how Rydel, drawing upon the history of nativity plays as well as their traditional text and character, created a sublime patriotic spectacle which later became a template for all subsequent literary nativity plays inspiriting Polish history and at the same time commenting on current affairs. Furthermore, the text presents Polish Bethlehem through the prism of modernist artists’ interest in the nativity scene as a literary genre and juxtaposes Rydel’s work with the nativity plays written by the Green Balloon Cabaret in order to show two significant directions in which this cultural phenomenon was evolving at the turn of the 20th century.